2018
DOI: 10.1111/gcb.14297
|View full text |Cite
|
Sign up to set email alerts
|

Solar‐induced chlorophyll fluorescence is strongly correlated with terrestrial photosynthesis for a wide variety of biomes: First global analysis based on OCO‐2 and flux tower observations

Abstract: Solar-induced chlorophyll fluorescence (SIF) has been increasingly used as a proxy for terrestrial gross primary productivity (GPP). Previous work mainly evaluated the relationship between satellite-observed SIF and gridded GPP products both based on coarse spatial resolutions. Finer resolution SIF (1.3 km × 2.25 km) measured from the Orbiting Carbon Observatory-2 (OCO-2) provides the first opportunity to examine the SIF-GPP relationship at the ecosystem scale using flux tower GPP data. However, it remains unc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

16
239
5
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 320 publications
(261 citation statements)
references
References 69 publications
16
239
5
1
Order By: Relevance
“…This higher \77/^_`2 value for ENF was also suggested by the comparison between OCO-2 SIF and FluxCom GPP dataset (Sun et al, 2018) and other comparisons using GOSAT SIF (Guanter et al, 2012). In consistent with (Li et al, 2018b), we also found small cross-biome 20 variation of GPP-SIF relationship. However, a large within-biome variation of \77/^_`2 is also found, which contributes to a large proportion of the observed cross-sites variations rather than the cross-biome variation.…”
Section: Cross-biome and Within-biome Gpp-csif Relationship 15supporting
confidence: 88%
“…This higher \77/^_`2 value for ENF was also suggested by the comparison between OCO-2 SIF and FluxCom GPP dataset (Sun et al, 2018) and other comparisons using GOSAT SIF (Guanter et al, 2012). In consistent with (Li et al, 2018b), we also found small cross-biome 20 variation of GPP-SIF relationship. However, a large within-biome variation of \77/^_`2 is also found, which contributes to a large proportion of the observed cross-sites variations rather than the cross-biome variation.…”
Section: Cross-biome and Within-biome Gpp-csif Relationship 15supporting
confidence: 88%
“…, Li, Xiao, He, Altaf Arain, et al (2018), and Sun et al (2017) conducted such investigations but used a limited number of EC sites, because the concurrent availability and consistent spatial footprints between OCO-2 SIF and EC sites were strongly limited by OCO-2's orbital gaps. First, its high-resolution and contiguous coverage will improve synergistic use of OCO-2 SIF with GPP from EC towers, such as Fluxnet and Long-Term Agroecosystem Research (LTAR) networks, facilitating mechanistic investigation of SIF-GPP relationships.…”
Section: Caveats and Potential New Applications With Sif Oco2_005mentioning
confidence: 99%
“…SIF has been found strongly correlated with the gross primary production (GPP) in a quasi‐linear pattern at large spatial and temporal scales (Frankenberg et al, ; Guanter et al, ; Li et al, ; Miao et al, ; Wood et al, ; Yang et al, ; K. Yang, Ryu, et al, ; Yang et al, ). Some studies suggest the potential of a universal GPP:SIF relationship across various biomes (Frankenberg et al, ; Li et al, ; Sun et al, ; but see Zhang et al, ), and others used SIF to constrain photosynthetic parameters (Guan et al, ; Perez‐Priego et al, ; Zhang et al, ; Zhang et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Likewise, SIF is the product of PAR in , fPAR, and fluorescence yield (SIF y ), in which the SIF y is an apparent parameter (equation ). Theoretically, SIF y can be defined as the product (SIF y = Φ f × f esc ) of the actual SIF y at the photosystem scale (Φ f ) and the escape ratio (f esc ) from the canopy (Guanter et al, ; Li et al, ). Practically, it is usually calculated by dividing SIF by PAR in ×fPAR (i.e., APAR).…”
Section: Introductionmentioning
confidence: 99%